Kombinasi Teknik Pembentukan Kokristal dan Ball milling untuk Peningkatan Disolusi Etoricoxib - Susanto, Sharon; Wikarsa, Saleh; Nugraha, Yuda Prasetya (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
Etoricoxib (ETX) is a selective COX-2 anti-inflammatory drug classified in BCS class II. This study aims to enhance the dissolution rate of etoricoxib through a combination of co-crystal formation and ball milling conducted in-situ and ex-situ. Optimization was done by varying milling times and types of stabilizers, including Tween 80 (ETX-OXA-BM-T), Poloxamer 188 (ETX-OXA-BM-P), and a combination of Tween 80-sodium lauryl sulfate (SLS) (ETX-OXA-BM-T-S). In-situ experiments yielded a very low yield (<10%) and failed to produce co-crystals, thus deeming them unsuitable for continuation. Meanwhile, the ex-situ process showed more potential, leading to further evaluation using Differential Scanning Calorimetry (DSC), Powder X-Ray Diffractometry (PXRD), and Scanning Electron Microscope (SEM). DSC analysis showed endothermic peaks at 130°C for ETX and around 179 - 180°C for ETX-OXA and its derivatives. PXRD diffractograms for ETX-OXA and its derivatives exhibited similar peaks, differing from ETX. SEM analysis indicated that ETX-OXA-BM-T with 60 minutes of milling resulted in nanometer-sized particles, while the use of Poloxamer 188 and the combination of Tween 80-SLS produced particle sizes > 1 µm. ETX-OXA-BM-T showed the highest increase in solubility in all media. The dissolution results of ETX-OXA-BM-T showed improvement in phosphate buffer pH 6.8, while no significant differences were observed in pH 1.2 and 4.5 buffers. This study demonstrates that the combination of co-crystal formation and ex-situ ball milling is a potential approach to enhancing the dissolution rate of etoricoxib.